2022
DOI: 10.1109/access.2022.3210189
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Anomaly Detection in Wireless Sensor Networks Based on Principal Component Analysis and Deep Convolution Neural Network

Abstract: With the popularity of wireless networks, wireless sensor networks (WSNs) have advanced rapidly, and their flexibility and ease of deployment have resulted in more security concerns, making it critical to research network intrusion prevention for WSNs. Denial of service (DoS) is a common network attack, achieving its goal by bringing down the target network. A DoS attack on WSNs devices with limited resources would be fatal. This paper proposes a method based on principal component analysis (PCA) and a deep co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The suggested model's classification results were evaluated using ROC curves, several evaluation parameters, and a confusion matrix to confirm validity. Regarding the classification effect, the suggested method has a reduced size and outperforms other traditional anomalous traffic detection models in experimental comparison [17].…”
Section: Literature Surveymentioning
confidence: 97%
See 1 more Smart Citation
“…The suggested model's classification results were evaluated using ROC curves, several evaluation parameters, and a confusion matrix to confirm validity. Regarding the classification effect, the suggested method has a reduced size and outperforms other traditional anomalous traffic detection models in experimental comparison [17].…”
Section: Literature Surveymentioning
confidence: 97%
“…Chengpeng Yao et al (2022) suggested design offers a compact framework along with improved feature extraction capabilities, allowing it to detect unusual network traffic on WSN systems with restricted storage space. The suggested model's classification results were evaluated using ROC curves, several evaluation parameters, and a confusion matrix to confirm validity.…”
Section: Literature Surveymentioning
confidence: 99%
“…Yao et al (27) the proposed study focuses on WSNs' susceptibility to assaults and their devices' limited storage capacity. To resolve this problem, the researchers suggest a new approach that associates PCA (Principle Component Analysis) with a DCNN for the purpose of detecting DoS traffic anomalies in WSNs.…”
Section: Related Workmentioning
confidence: 99%
“…At last, robust IDS using LSTM is implemented on the CHs. Yao et al [15] suggest a technique based on DCNN and principal component analysis (PCA) for traffic anomaly detection of DoS in WSN, depending on the WSN vulnerability to attacks and the restricted memory capacity of their devices. The presented algorithm has a more effective capability of feature extraction and lightweight structure that could successfully identify network abnormal traffic in WSN with restricted memory capacity.…”
Section: Related Workmentioning
confidence: 99%